16th November Proper 28: Zephaniah 1.7, 12-18; Matthew 25.14-30 - Randles, Viv (2014)
The article presents a sermon for November 16, 2014 about reconciling Christians' images of God. It references an image manipulation program called Identikit wherein it presents photographs of people wanted for crimes publicised on "Police 5" or "Junior Police 5." Topics discussed include the challenge of reconciling images of God amidst personal struggles, doubts and trials, and the images of God presented as shepherd, and as a God of judgement.
Keywords: Bibel; Anvertrautes Geld; Bibel; Criminals; Image of God; Image (Theology); Shepherds